Respuesta :
-x^2 -3x + 2
------------------------------
-3x ) 3x^3 + 9x^2 - 6x
3x^3
9x^2
-6x
answer is -x^2 - 3x + 2
------------------------------
-3x ) 3x^3 + 9x^2 - 6x
3x^3
9x^2
-6x
answer is -x^2 - 3x + 2
Answer:
Quotient = -x² -3x +2.
Step-by-step explanation:
Given : quantity of 3 times x to the 3rd power plus 9 times x to the 2nd power minus 6 times x all over negative 3 times x.
To find : Find the quotient.
Solution : We have given that statement
3 times x to the 3rd power = 3x³.
9 times x to the 2nd power =9x²
6 times x = 6x
3x³ +9x²-6x over -3x.
On dividing 3x³ +9x²-6x by -3x
[tex]\frac{3x^{3}}{-3x} +\frac{9x^{2}}{-3x} -\frac{6x}{-3x}[/tex] .
On cancel out the like numertor and denominator.
Quotient = -x² -3x +2
Therefore, Quotient = -x² -3x +2.